AUDIT TATA KELOLA DAN MANAJEMEN RISIKO TEKNOLOGI INFORMASI PADA WEBSITE KANTOR CAMAT PAYUNG SEKAKI MENGGUNAKAN FRAMEWORK COBIT 2019 - Jamali, Raihan Hafidz; Zaenal Arifin; Megawati (Jurnal Rekayasa Sistem Informasi dan Teknologi, 2025)
The rapid development of information technology requires every agency, including government agencies, to manage IT effectively and efficiently to improve the quality of public services. One form of IT utilization is the implementation of a web-based public complaint information system, such as that carried out by the Payung Sekaki Sub-district Office. However, the absence of a formal evaluation based on the IT governance framework raises the need for an information system audit. This research aims to evaluate IT governance and risk management using the COBIT 2019 framework, specifically in domains APO01 (Managed I&T Management Framework) and APO12 (Managed Risk). The research method used is a qualitative approach with observation, interview, and questionnaire techniques. The results of the capability level measurement show that both domains are at Level 2 (Managed Process), which means that the process has been carried out but has not been formally documented and periodic evaluations have not been carried out. This research provides recommendations in the form of formal SOP preparation, regular training, and periodic evaluation as an effort to improve IT governance capabilities.